The Problem of Technology in Maruyama Masao's Notion of Modernity in Japan's "Overcoming of Modernity" Debate in 1972 - Takao, Koga (2017)
The purpose of this essay is to rethink the meaning of modernity through an examination of Maruyama's defense of modernity during the "Overcoming of Modernity" Debate in Japan in 1942. I will initially propose that Maruyama understood the opponents of modernity as ultra-nationalists who were merely defending an ideological justification for Japan's war. However, Maruyama defined "modern thinking" (kindaiteki shii) in terms of personal autonomy. His understanding of modernity as a mental attitude led to his failure to consider the technological aspects of this debate. After considering the various intellectual positions on this issue, I shall argue that a democratic control of technology must be presupposed in Maruyama's defense of modernity.
Keywords: Maruyama Masao; Modernity; Autonomy; Totalitarianism; Socialism; Japan